KEDUDUKAN PENGEMBANG DALAM PELAKSANAAN JAMINAN PEMBELIAN (BUYBACK GURANTEE) KEMBALI SEBAGAI AKIBAT GAGAL BAYAR DEBITUR PADA KREDIT KEPEMILIKAN APARTEMEN - Idrian; Lutfi, Anas (Faculty of Law, University of Mataram, 2024)
The need for housing in urban areas with limited land encourages the development of integrated housing with business centers, supported by banks that offer Apartment Ownership Loans. Banks play an important role in channeling public funds, facilitating financing that benefits banks, developers, and buyers. However, consumers often experience defaults. The Repurchase Guarantee Agreement allows the developer to buy back the sold unit as per Article 1519 of the Civil Code. Although consumer rights are often discussed, the rights of developers who comply with regulations receive less attention. This research aims to identify and analyze the implementation of the repurchase guarantee, the underlying factors of the repurchase guarantee, the legal framework for the implementation of the repurchase guarantee, as well as efforts to resolve disputes between developers and debtors related to the implementation of subrogation deeds. This research uses a normative juridical method. Data sources include primary legal materials (such as the Civil Code and several related laws), secondary legal materials (textbooks and law journals), as well as non-legal materials (dictionaries and encyclopedias). Data analysis techniques include identification of legal facts, collection of relevant materials, review of legal issues, drawing conclusions, and providing prescriptions, using the deductive method.